The spread of digital social networks and the new expressions of the self - Germano, Idilva Maria Pires; Gabriele Moura, Maria Camila (Revista de Psicologia, 2017)
The social and technological changes brought by the internet and the increasingly wide dissemination of social networks introduced new narrative phenomenona, whose proportions radiate and establish a new discursive pattern. The present work has the scope of analysis about the new way of narrating itself in the so-called Digital Age, demonstrating the emergence and evolution of these new narratives and situating them in the present historical moment, strongly marked by a new logic of consumption, information and communication. In addition, the study sought to map the nature of these narratives as autobiographical reports, bringing to the surface, beyond the contours of the narrator and the narrated object, the problematization of spontaneous overexposure of the individual’s image in social networks. Finally, we try to discuss the possible limits of such overexposure, whose delimitation is still in the process of construction, before which ethical issues begin to be raised and discussed.